Radon transport from soil to air and Monte-Carlo simulation. (January 2022) - Muhammad, Ahmad; Külahcı, Fatih
Abstract: The exhalation of geochemical entities from soil to air is significant to understand Lithosphere-Atmospheric relationships. Some of these geochemical entities are capable of modifying the lower atmosphere, and they are employed in various studies. Radon is one of the geochemical gasses widely recognized as a dominant ionization source in near ground regions of the troposphere. The steady state Rn transport equation is considered in many cases for estimating Rn migration from soil to air on the condition that the time evolution is ignored. A method is proposed for estimating radon space-time transport from soil to air. This is achieved by solving the radon transport equation in soil with special boundary conditions. Similar results are obtained with some experimented models, as well as reported radon values in literature for some set of parameter combinations. Strengths and limitations of the method are discussed. The model is useable to study Lithosphere-Atmosphere relationships. It can also be significant in other studies like the Global Electric Circuit or Seismo-Ionospheric studies. Highlights: An improved method is presented for estimating radon space-time transport from soil to air. The model can be significant in studying Lithosphere-Atmosphere relationships.